Tortall : a spy's guide - Pierce, Tamora; Holderman, Julie; Liebe, Timothy; Messinger, Megan (Random House, 2017)
Tortall's spymaster, George Cooper, cleans out his office and finds letters, notes, character profiles, family papers, and more that reveal the secrets of Tortall. Includes a timeline.